Genetic differentiation analysis of African cassava (Manihot esculenta) landraces and elite germplasm using amplified fragment length polymorphism and simple sequence repeat markers - Raji, A.A.J.; Fawole, I.; Gedil, Melaku A; Dixon, Alfred G.O. (Wiley, 2009)
Molecular-marker-aided evaluation of germplasm plays an important role indefining the genetic diversity of plant genotypes for genetic and populationimprovement studies. A collection of African cassava landraces and elite culti-vars was analysed for genetic diversity using 20 amplified fragment length poly-morphic (AFLP) DNA primer combinations and 50 simple sequence repeat (SSR)markers. Within-population diversity estimates obtained with both markerswere correlated, showing little variation in their fixation index. The amountof within-population variation was higher for landraces as illustrated by bothmarkers, allowing discrimination among accessions along their geographicalorigins, with some overlap indicating the pattern of germplasm movementbetween countries. Elite cultivars were grouped in most cases in agreementwith their pedigree and showed a narrow genetic variation. Both SSR andAFLP markers showed some similarity in results for the landraces, althoughSSR provided better genetic differentiation estimates. Genetic differentiation(Fst) in the landrace population was 0.746 for SSR and 0.656 for AFLP. Themolecular variance among cultivars in both populations accounted for up to83% of the overall variation, while 17% was found within populations. Genediversity (He) estimated within each population varied with an average valueof 0.607 for the landraces and 0.594 for the elite lines. Analyses of SSR datausing ordination techniques identified additional cluster groups not detectedby AFLP and also captured maximum variation within and between both pop-ulations. Our results indicate the importance of SSR and AFLP as efficientmarkers for the analysis of genetic diversity and population structure in cas-sava. Genetic differentiation analysis of the evaluated populations provideshigh prospects for identifying diverse parental combinations for the develop-ment of segregating populations for genetic studies and the introgression ofdesirable genes from diverse sources into the existing genetic base